Maternal mortality in rural Gambia: levels, causes and contributing factors - G. Walraven; M. Telfer; J. Rowley; C. Ronsmans (The World Health Organization, 2000)
A demographic study carried out in a rural area of the Gambia between January 1993 and December 1998 recorded 74 deaths among women aged 15-49 years. Reported here is an estimation of maternal mortality among these 74 deaths based on a survey of reproductive age mortality, which identified 18 maternal deaths by verbal autopsy. Over the same period there were 4245 live births in the study area, giving a maternal mortality ratio of 424 per 100 000 live births. This maternal mortality estimate is substantially lower than estimates made in the 1980s, which ranged from 1005 to 2362 per 100 000 live births, in the same area. A total of 9 of the 18 deaths had a direct obstetric cause - haemorrhage (6 deaths), early pregnancy (2), and obstructed labour (1). Indirect causes of obstetric deaths were anaemia (4 deaths), hepatitis (1), and undetermined (4). Low standards of health care for obstetric referrals, failure to recognize the severity of the problem at the community level, delays in starting the decision-making process to seek health care, lack of transport, and substandard primary health care were identified more than once as probable or possible contributing factors to these maternal deaths.